Hygiene Awareness and Compliance Among Culinary Students at Widya Praja Ungaran Vocational School - Irma Winari; Muhammad Ansori (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Food is a primary human need, therefore food hygiene and safety must be properly maintained, especially by food handlers. This study's goal is to explore the correlation between awareness and hygiene compliance of Culinary students. A quantitative approach was applied in this study through the use of a descriptive-correlational method designed to ascertain the correlation between awareness and hygiene compliance among culinary students. The research subjects consisted of 35 tenth-grade Culinary students of Widya Praja Vocational School selected through total sampling (n = 31). The research instrument includes a 24-item questionnaire to measure hygiene awareness and an observation sheet to assess hygiene behavior compliance. Instrument testing was conducted using SPSS version 27. The instrument was considered valid if r-count (>0,355) and reliable if Cronbach’s Alpha > 0,60. The reliability test revealed Cronbach's Alpha value of 0,937, revealing that the instrument was reliable. The findings revealed that the average student’s hygiene awareness score was 93%, while the average hygiene compliance score was 93,3%, both categorized as very high. Pearson correlation analysis showed an r value of 0,900 with a significance level of p < 0,001. These results reveal a very strong and significant correlation between hygiene awareness and hygiene behavior compliance. This study was limited to one school with a relatively small number of respondents and did not examine other factors that may influence a student's hygiene behavior.